2018
DOI: 10.1089/cyber.2017.0586
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and Cyberbullying Across Adolescence

Abstract: Cyberbullying perpetration continues to be a prevalent and harmful phenomenon. Despite the recent wealth of studies that examine cyberbullying frequency, further research is needed to investigate protective factors or variables that decrease the likelihood of engaging in cyberbullying perpetration. Past work has identified certain types of parenting as a potential protective factor against adolescent cyberbullying perpetration; however, there is a paucity of research testing these relations over time. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
44
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 41 publications
4
44
1
3
Order By: Relevance
“…More specifically, Govender and Young (2018) noted that authoritarian parenting was significantly and moderately correlated with cyberbullying perpetration. These results agree with those obtained by Zurcher et al (2018), who reported that authoritarian parenting behaviors served as a risk factor for cyberbullying perpetration, particularly for boys. They also coincide with the findings of the research conducted by Shams et al (2017), who indicated that children of authoritarian parents were more likely to be bullied by other students (cyber and traditional victimization was included).…”
Section: Parental Educational Stylessupporting
confidence: 92%
See 3 more Smart Citations
“…More specifically, Govender and Young (2018) noted that authoritarian parenting was significantly and moderately correlated with cyberbullying perpetration. These results agree with those obtained by Zurcher et al (2018), who reported that authoritarian parenting behaviors served as a risk factor for cyberbullying perpetration, particularly for boys. They also coincide with the findings of the research conducted by Shams et al (2017), who indicated that children of authoritarian parents were more likely to be bullied by other students (cyber and traditional victimization was included).…”
Section: Parental Educational Stylessupporting
confidence: 92%
“…Their findings also indicated that children in the non-violent group were more likely to perceive their parents' style of parenting as authoritative and authoritarian, and victim-perpetrators as permissive and laissez-faire. Finally, Zurcher et al (2018) also concluded that the authoritative parenting style, specifically the warmth and support dimension, was associated with lower levels of cyberbullying perpetration. 3.2.5.…”
Section: Parental Educational Stylesmentioning
confidence: 93%
See 2 more Smart Citations
“…Two other potential adverse effects of social media include addiction and cyberbullying. 4,5 As with other forms of addiction, such as addictions to alcohol or gambling, social media can provide that little dose of positive reinforcement every time a "like" or a notification of some sort is received. [6][7][8] Needing these positive reinforcements can add to "fear of missing out" (FOMO), the concern or anxiety that others might be having rewarding experiences from which one is absent.…”
mentioning
confidence: 99%